Designing Reading Side as Educational Application for Senior High School Learners - Rohmat Hidayat; Ulfa Wulan Agustina; Muchamad Rahman Bagus Tohari (UIBU, 2025)
The utilization of ICT (Information and Communication Technology) based learning media has become a significant factor in enhancing the usefulness and efficiency of the learning process. The objective of this research is to develop R-SIDE applications and to test the usefulness of it for use by senior high school students. The researchers employed the research and development (R&D) method. This method comprises five stages: analysis, design, development, implementation, and evaluation. The data were collected using two instruments: observation and questionnaire. Prior to implementation, the R-SIDE applications were validated by four experts, comprising two material experts and two media experts. The material expert validators indicated a level of agreement with the items in the